Pengaruh Toksisitas Timbal Asetat Pb(CH3COO) Dan Kepadatan Terhadap Perubahan Warna Dan Persentase Anakan Jantan Kutu Air Daphnia sp. - Ariestyanto Eka Putera; Andi Rahmad Rahim; Firma Fika Rahmawati (Jurnal Perikanan Pantura (JPP), 2018)
Pb (CH3COO) was a metal that could accumulated in organisms tissue. Pb contents in organismstissue increased by increasing of Pb (CH3COO) concentration in the water and the durationorganisms that live in water pollution by Pb (CH3COO). It is caused organisms did not regulatedby Pb (CH3COO) one that turns in at organisms body. Daphnia sp.are sensitive to the chemicalin the waters ecology and has an important role in the ecology of freshwater as the first of trophiclevel in the waters ecology. The objective of this study was to obtain information about effect theconcentration of heavy metals Pb (CH3COO) in differences densities of Daphnia sp.to colorchanges and percentage of male larvae Daphnia sp. This research design uses factorial cmpleterandoms design. The main parameter in this research is color changing and male larvae on theDaphnia sp. While supporting parameters in this research is water quality (temperature, pH,amonia and DO). The result of research indicates that the heavy metal Pb (CH3COO) withdifferent concentration to the adult female Daphnia sp. showed significantly difference (p<0,05)of the Daphnia sp. color change, the highest density of Daphnia sp. (400 Daphnias) with heavymetal concentration 3.16 mg/l.